Soil nutrient measurement in paddy farming using IoT - Goutham Chand, K; Sidhendra, M; Mohammed Ali Hussain, Dr (International Journal of Engineering and Technology, 2018)
In India agriculture is a major factor in the development of an economy. It plays a major role in eradicating the world hunger, but farmers in India still use primitive and old ways to grow their crops especially paddy which even though is not wrong but doesnâ€™t help farmers to get the maximum yield out of their paddy farms. To do that they need to utilize the modern technology that will not only help them increase their paddy yield but also reduce their dependency on weather conditions and also on manual labor. One such technology is discussed in this paper, here we are proposing a way to measure soil nutrients in real time and send that data to the farmer so that he can plan the type of seed for paddy crop he wants to grow for that season. This paper mainly measures nitrogen phosphorous potassium (NPK) in the soil which means nitrogen sodium and potassium which are major micronutrients in the soil. Farmers start using fertilizers which are not only harmful to the environment but also are damaging to the humans and animals who consume them. Not only do we provide a way to avoid this but also help the farmers which variety of seed to a farm to increase their yield. We also send a notification to the farmerâ€™s phone about the values in the soil and also the market values of the paddy crop they are farming in particular season.Â